Plan de marketing para la empresa “Aceros del Sur” de la ciudad de Loja - Medina Contento, María Rosario (2016)
At the moment the companies have a without number of obstacles q they impede their process and good operation, the government laws, the more and more unstable economy and the competitiveness that it exists in the means are some of the most important, for the q the managers are come in the obligation from investigating means and necessary strategies for the appropriate acting from the company to their position. The base of study of the present investigative work is focused especially in the elaboration of a plan of strategic marketing, taking in consideration the characteristics of the clients (habits of purchases, likes and preferences, etc.) characteristic of the products, the situation of the competition and the possibilities of enlarging the sales always pointing to get the full satisfaction of the clients whose purpose is to generate a bigger number of clients and for ende to get a positioning, as well as to achieve an excellent attention and mainly to be able to offer to the community an efficient and opportune service. The methods q was used for the investigation they are the deductive, inductive, descriptive method and the historical one which were good us for the development d the present investigation. To be able to determine the analysis of the company, firstly it was opted to carry out the collection of data, so much internal as external of the company, through the realized surveys to 384 clients and 4 employees, use of the direct observation was also made to verify in a real way the conditions in which the activities of commercialization of the company STEELS OF THE SOUTH are developed in our city, determining through this, the changes to carry out. The tabulation, analysis of surveys and direct observation allowed to obtain extensive information on the investigation of research, this research helped to establish the Situational diagnosis where determined factor economic, technological, socio-cultural, political, environmental, as well Porter's five forces analysis, likewise the preparation of competitive profile matrix which allowed us to identify the main competitors of the company, as well as its strengths and weaknesses, in relation to a sample of the company strategic position, also presents the analysis of the BCG matrix relating to the company in study to then present the main FODA, this analysis resulted in of the proposal for a plan of marketing en South Steels of the city of Loja, and for its correct application must apply four objectives concerning the development of the business through the development philosophy of the mission and vision of the company at a cost of $ 23.00, the second objective make a plan of advertising the vents at a cost of $ 654.00, the third objective a training plan to motivate staff at a cost of $340.00, and offer a better service, and finally, a fourth objective develop a promotion plan to motivate customers with a cost of $ 1025.00 the total cost of this marketing plan is $ 2042.00. To complete this work suggests the conclusions and propose recommendations, aimed at ameliorating the problems found.